Synthesis and Diagnosis New Metallotropic LCs from Organotin (IV) Complex - Mohammed Hussein; Alaa Adnan Rashad; Hamsa Thamer; Alaa Mohammed; Ali H. Jawad; Emad Yousif (Al-Qadisiyah Journal of Pure Science, 2021)
Organotin (IV) complex is part of the organometallic chemistry and in recently decades have a variety of interesting and application used it. A new class of metallomesogens LC (A) Ph3Sn(VAL), (B) Bu3Sn(VAL), (C) Ph2Sn(VAL)2 and (D) Bu2Sn(VAL)2 was synthesis through the reaction of valsartan ligand with (di- or tri- butyl tin chloride salt) and (di- or tri- phenyl tin chloride salt) in methanol solvent. 1H NMR,119 Sn NMR, FTIR and CHN elemental analyses were measure and the liquid crystalline properties were study by POM. The mesophase in all organotin (IV) carboxylate complexes are thermotropic nematic phase. In complexes (A, C) the optical textures of A show a typical droplet texture and thread shape LC phase transition between (400-440⁰C) higher than mesophase textures in C between (230 -250⁰C). In complexes (B, D) the optical textures of B appearance a thread shape and the LC phase transition temperature between (200 -400⁰C) and in D thread shape and the transition temperature beginning up to 280⁰C. From a temperature of phase transition show that the complexes (C, D) are start liquid crystal mesophase in lower than complex (A, C) because effect of R-group and types which due to an asymmetric arrangement of the molecule and a geometry was calamitic in which the length of the molecule is major in compare with its diameter.